Profile of fatal electrocution cases in Ballari, Karnataka, India - Charan Kishor, Shetty; Biradar, Gururaj; Satish, Babu; Vaddinakatti, Yogiraj; Pavanchand, Shetty (2017)
Background: Death by electrocution may not be a major cause of unnatural deaths, but still accounts for a sizeable number of deaths around the world. It is usually accidental in manner. In a developing country like India, electrocution continues to be a significant cause of unnatural deaths. This study was designed to identify the trends and characteristics of electrocution deaths in Ballari region of South India. Methods: The relevant data were obtained from the Department of Forensic Medicine and Toxicology, Vijayanagar Institute of Medical Sciences (V.I.M.S), Ballari, Karnataka, India from 2010 through 2016. Results: Based on our study, males aged from 21 to 30 years were the most victims of fatal electrocution. These deaths were highest during the months of September to December and commonly occurred during the day time. The limbs were the most commonly effected body parts. Most cases were accidental in nature while contact with the electric pole being the main source of those accidents. Conclusion: The study may help enhance public awareness of electrocution deaths. It will also help the enforcement agencies implement strategies to avert such unnatural deaths.